KOMPARASI SISTEM MANUFAKTUR PUSH DAN PULL MELALUI PENDEKATAN SIMULASI - Eric Wibisono (Institute of Research and Community Outreach - Petra Christian University, 2004)
Manufacturing systems that are often classified as push and pull often invite question: